RESPON PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH ( Capsicum annum L.) TERHADAP KONSENTRASI PEMBERIAN PUPUK ORGANIK CAIR DARI LIMBAH WORTEL - Sartika Putri; Kartika Manalu; Rahmadina Rahmadina (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2020)
The study aims to know the worthiness of liquid organic fertilizer derived from carrot waste, knowing the effect that liquid organic fertilizer derived from carrot waste has on the growth and output of the pepper plant (Capsicum annum L.) and to find out how much organic fertilizer sewage does to the growth and output of the pepper plant (Capsicum annum L.). the methods used in this study are full random design (RAL) in this study using 5 treatment and 5 times Deuteronomy with 0% treatment as control treatment B 5%, treatment C 10%, treatment D 15%, and treatment E 20%. The parameters used were the height of the plant, the number of leaves, the number of branches, the number of flowers and the number of fruits. Data results from the analysis using statistical product and service solutions (SPSS) version 23. Results showed content found in the organic fertilizer of carrot waste C-organic (0.86%), Nitrogen (1.14%), Phospor (0.01%), potassium (0.18%), and c/n ratio (0.76%). Studies already conducted can be proved that giving organic fertilizer in carrot waste at 5%, 10%, 15%, and 20% affecting the plant’s heighest average value of the plant 5% is 36.5, the highest rate of leaves at 5% concentrations of 38.6, the highest rate of branches at 15% concentration of 11.8, the highest rate of interest at 5% concentration of 11, and the amount of fruit with an average value at 8.giving the most optimal amount of organic fertilizer from carrot waste at 5% and 15%.